The Cambridge handbook of instructional feedback - Lipnevich, Anastasiya A.; Smith, Jeffrey K. (Cambridge handbooks in psychology, 2018)
"'Feedback, like rain, should be gentle enough to nourish a person's growth without destroying the roots.' This quote (modified from the original by Frank A. Clark) is a simple reminder that feedback can be helpful or not, assume a variety of forms, be provided at different times, and have diverse effects on different people. But what if there were a drought (no rain, no feedback)? Consider the following two questions: If a tree falls in the woods and nobody's around to hear it...does it make a noise? If a teacher instructs some content or skill and doesn't assess and support learning...can students deeply learn? In both cases, the answer is no. So feedback is really important...not just for learning new things, but pretty much across all of life. There are countless examples of feedback in nature...with both positive and negative functions. For example, our hypothalamus reacts to changes in temperature and responds appropriately. If the temperature drops, we shiver to bring up the temperature; and if it's too hot, we sweat to cool down via evaporation. Predator-prey relations in nature are also well-known examples of feedback loops, as is climate change. The key difference between positive and negative feedback is their response to change...positive feedback enlarges change while negative feedback reduces change"...